VERTICAL MIXING OF WATER MASS IN BANDA SEA AND TIMOR SEA - Wijayanti, Reni
Vertical mixing is a process of water mass mixing that occur vertically. The purpose of this research is to see how the process of vertical mixing that occur in the Banda Sea and Timor Sea by looking at their water mass characterisctics, Richardson Number (Ri) and Vertical Diffusivity (Kz) to show how profound the vertical mixing. This study uses temperature, salinity and depth data from CTD (Conductivity Temperature and Depth) of Banda Sea Expedition during 21-28 October 2013 by Indonesian Institute of Science in Ambon. Banda Sea data consists of 20 stations that spread across the Banda Sea and arranged in 4 transects depend of their latitude position. Timor Sea data consist of temperature, salinity and depth from CTD and meridional & zonal current velocity from ADCP (Accoustics Current Doppler Profiler) during 10-15 May 2010 of Arafura and Timor Sea Ecosystem Action (ATSEA) cruise. Timor Sea data consist of 12 stasions that spread across the Timor Sea and arranged in 4 transects. The results show that there are 8 water masses identified in both Banda Sea and Timor Sea such as SPIW (South Pacific Intermediete Water), AAIW (Antartic Intermediete Water), PEW (Pacific Equatorial Water), ESPW (Eastern South Pacific Water), WSPW (Western South Pacific Water), WNPW (Western North Pacific Water), ENPW (Eastern North Pacific Water) and AAMW (Austalasian Mediterranean Water). Vertical mixing in Banda Sea indicated by the vertical diffusivity value (Kz = 7.40 x10-3 m2s-1). Vertical mixing in Timor Sea indicated by vertical diffusivity values (Kz = 1.33 x10-2 m2s-1) and Richardson Numbers (Ri = 1.61x10-4). A large vertical diffusivity value indicates the existence of the ITF (Indonesian Throughflow) that pass through the Banda Sea and Timor Sea.